Evaluasi Kualitas Dan Kepuasan Pengguna Website Imissu Dengan Penerapan Metode Webqual 4.0 - Putra, I Ketut Citra Adi; Saputra, Komang Oka; Ariastina, Wayan Gede (Majalah Ilmiah Teknologi Elektro, 2019)
Use of Information Technology in academic activities now utilizes integrated information systems. Udayana University has used information technology on academic services into an SSO service (Single Sign On) named IMISSU. This study aims to evaluate the quality and satisfaction of IMISSU website users. The research method used a cross sectional design with a descriptive type of research. The researcher used primary data by taking data using a questionnaire. The sampling technique used in sampling is a non-probability sampling technique with an accidental sampling approach, the number of respondents obtained is 121. Data analysis was performed using the Spearman rank test. The results of the study show a high relationship between the quality of usability and user satisfaction.